2003
DOI: 10.1038/nn1104
|View full text |Cite
|
Sign up to set email alerts
|

Lmx1b is essential for the development of serotonergic neurons

Abstract: The specification and differentiation of serotonergic (5-HT) neurons require both extrinsic signaling molecules and intrinsic transcription factors to work in concert or in cascade. Here we identify the genetic cascades that control the specification and differentiation of 5-HT neurons in mice. A major determinant in the cascades is an LIM homeodomain-containing gene, Lmx1b, which is required for the development of all 5-HT neurons in the central nervous system. Our results suggest that, during development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
234
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(253 citation statements)
references
References 26 publications
14
234
1
4
Order By: Relevance
“…In situ hybridization was performed as previously described (19). For the mouse MOR probe, the MOR plasmid was cut with HindIII and transcribed with SP6 RNA polymerase to produce the antisense cRNA probe (53).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridization was performed as previously described (19). For the mouse MOR probe, the MOR plasmid was cut with HindIII and transcribed with SP6 RNA polymerase to produce the antisense cRNA probe (53).…”
Section: Methodsmentioning
confidence: 99%
“…We have generated a line of conditional knockout mice called Lmx1b f/f/p mice in which the transcription factor Lmx1b, which is essential for the development of 5-HT neurons in the hindbrain, is selectively deleted in cells expressing Pet1 (19)(20)(21). Because 5-HT neurons lacking Lmx1b fail to survive, the deletion of Lmx1b results in the specific loss of the central 5-HT neurons in Lmx1b f/f/p mice (21).…”
mentioning
confidence: 99%
“…While genetic inactivation of the upstream transcription factors Lmx1b and Pet1 compromises the development of the majority of 5-HT neurons [16, 17,51], it is concluded that intrinsic 5-HT production is neither essential for the development maintenance and survival of serotonergic neurons, nor for the molecular specification of a serotonergic-like phenotype. This further suggests that the developmental role of 5-HT in the maturation/differentiation of the 5-HT system itself has been overvalued, and the notion of an autoregulation of 5-HT system development [6,7] may need to be addressed from a new standpoint.…”
Section: Tph2 In Personality Traits Of Negative Emotionality and In Dmentioning
confidence: 99%
“…Additionally, 5HT neurotransmission is modulated through abundant afferent information arising from, for example, other monoaminergic systems (8,9) and from orexinergic, glutamatergic, and GABAergic pathways (10)(11)(12). The remarkably expansive neuromodulatory influence of 5HT is the product of a complex transcriptional cascade that generates 5HT-synthesizing neurons in the ventral hindbrain (13)(14)(15)(16)(17)(18). 5HT also figures prominently in mental health disorders as a number of lines of evidence provide strong support for the hypothesis that altered serotonergic signaling contributes to neurological and psychiatric pathogenesis (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Recent gene-targeting studies of 5HT neurons are also limited in that most of the targeted genes reported to date are ubiquitously expressed and play essential roles in early development. Consequently, propagation of their homozygous null alleles in the mouse results in embryonic or early postnatal death (13,17). Thus, an approach to conveniently alter gene expression in a 5HT neuron-specific manner would greatly facilitate studies of the 5HT transmitter system.…”
mentioning
confidence: 99%